De-radicalization Program: The Case Study of Indonesia - Yaza Azzahara Ulyana; Ahmad Riyansyah (Research Collaboration Community (RCC), 2021)
Deradicalization program has emerged since 2012 by Indonesian Government due to the fact of increasing number of terrorism act happened in Indonesia. Indonesian government imposed the soft approach in order to be able to rehabilitate terrorist, its group, and family from radical mindset effectively. The ex-convicted terrorist is expected to disengage from their previous group and mindset and ready to rejuvenate as a new person with a moderate mind so that they can mingle back to the society. The program that applied by BNPT is comprehensively for all ages the only differences is when encountered the youth so the approach is slightly different. The purpose of this study is to describe and explaining the formulation of Indonesian deradicalization program in detail. This study uses a social identity theory in explaining the formulation and implementation of BNPT de-radicalization program. In this study, the author used qualitative methods with explanatory research type, followed by collecting data through literature. Based on existing findings, the deradicalization program, which rooted in social identity basic assumptions, is comprehensively established without discrediting certain religious values. And the de-radicalization program in Indonesia can be regarded as successful if the number of people turning back to the radical acts is low. So that to create a sustainable effort BNPT should promote the program more harmoniously, to ensure the effectiveness of the rehabilitation program.